Pleural mesothelial cells in pleural and lung diseases - Batra, Hitesh; Antony, Veena B. (Journal of Thoracic Disease; Vol 7, No 6 (June 08, 2015): Journal of Thoracic Disease (Advances and Controversies in Pleural Diseases), 2015)
During development, the mesoderm maintains a complex relationship with the developing endoderm giving rise to the mature lung. Pleural mesothelial cells (PMCs) derived from the mesoderm play a key role during the development of the lung. The pleural mesothelium differentiates to give rise to the endothelium and smooth muscle cells via epithelial-to-mesenchymal transition (EMT). An aberrant recapitulation of such developmental pathways can play an important role in the pathogenesis of disease processes such as idiopathic pulmonary fibrosis (IPF). The PMC is the central component of the immune responses of the pleura. When exposed to noxious stimuli, it demonstrates innate immune responses such as Toll-like receptor (TLR) recognition of pathogen associated molecular patterns as well as causes the release of several cytokines to activate adaptive immune responses. Development of pleural effusions occurs due to an imbalance in the dynamic interaction between junctional proteins, n-cadherin and β-catenin, and phosphorylation of adherens junctions between PMCs, which is caused in part by vascular endothelial growth factor (VEGF) released by PMCs. PMCs play an important role in defense mechanisms against bacterial and mycobacterial pleural infections, and in pathogenesis of malignant pleural effusion, asbestos related pleural disease and malignant pleural mesothelioma. PMCs also play a key role in the resolution of inflammation, which can occur with or without fibrosis. Fibrosis occurs as a result of disordered fibrin turnover and due to the effects of cytokines such as transforming growth factor-β, platelet-derived growth factor (PDGF), and basic fibroblast growth factor; which are released by PMCs. Recent studies have demonstrated a role for PMCs in the pathogenesis of IPF suggesting their potential as a cellular biomarker of disease activity and as a possible therapeutic target. Pleural-based therapies targeting PMCs for treatment of IPF and other lung diseases need further exploration.